Removal of 6 months old 9 cm long wooden foreign body from forearm of 40 year old male: a case report - Vaghani, Sanjay G.; Juneja, Mansi J.; Katwala, Priyank K. (International Surgery Journal, 2019)
Injuries to hand are common at work. Most of them are noticeable and can be managed. Complete foreign body removal depends on location and mechanism of injury. There are few reports of accidental injury by foreign body followed by delayed retrival of foreign body. We report this case of delayed removal of foreign body after 6 months hoping to expand the literature and to provide insight to prevent septic complications by early prompt detection and removal of foreign bodies.